Differences in Ethnic/Racial Diversity of Texas Community College First-Time in College Full-Time Students Over Time: A Multiyear, Statewide Analysis - Lebron, Juan Carlos; Slate, John R; Lunenburg, Frederick C (Asian Journal of Interdisciplinary Research, 2020)
In this multiyear, statewide empirical investigation, the degree to which ethnic/racial diversity of first-time in college full-time Texas community college students changed from the 1999-2000 through the 2014-2015 academic years was determined. Over this time period, the percentage of Hispanic first-time in college full-time Texas community college students showed a statistically significant increase, whereas the percentage of White first-time in college full-time students statistically significantly decreased. No changes were noted with respect to either Black or Asian first-time in college full-time college students during this time period. Although some improvement was noted in the ethnic-racial diversity of Texas first-time in college full-time students, more work remains. Implications for policy and recommendations for research were provided.